Biomechanical comparison of plate, intramedullary screw, and headless compression screw fixation in Danis–Weber type B lateral malleolar fractures - Chen-Yuan Yang; Wei-Chun Hong; Ming-Tzu Tsai; Jui-Ting Hsu (Journal of Orthopaedic Surgery and Research)
Abstract Background Weber type B transsyndesmotic fractures are the most common type of lateral malleolar fractures, a common ankle fracture type. Although several surgical techniques are available for fixation, no clinical consensus exists regarding the optimal fixation method. Objective This study evaluated the biomechanical differences in fixation stability among one-third tubular plates, 3.5-mm intramedullary screws, and 4.5-mm intramedullary headless compression screws for Weber type B lateral malleolar fractures using an in Vitro mechanical analysis. Materials and methods In total, 24 artificial fibula bone specimens were used. The specimens were subjected to Weber type B lateral malleolar fractures using a saw blade and randomly divided into three groups treated with different fixation methods, with eight specimens per group: (1) One-third tubular plate, (2) 3.5-mm intramedullary screw, and (3) 4.5-mm intramedullary headless compression screw. The specimens were subjected to bending and torsional mechanical testing using a materials testing system. The bending test was evaluated using 10-mm displacement force (Newtons) and bending stiffness (Newtons/millimeter) as the assessment parameters. For the torsional test, 20° rotation torque (Newtons/millimeter) and torsional stiffness (Newton∙millimeters/degree) were used as evaluation parameters. The experimental results were analyzed using the Kruskal–Wallis test. When significant differences were found, post hoc pairwise comparisons were conducted using the Dunn–Bonferroni approach. Results In the bending test, no statistical differences were observed between the three fixation methods, whether evaluated by 10-mm displacement force or bending stiffness. Nevertheless, for the 20° rotation torque assessment in the torsional test, both the one-third tubular plate (1360.31 ± 221.56 N·mm, median ± interquartile range) and the 4.5-mm intramedullary headless compression screw (1420.41 ± 281.95 N·mm) exhibited similar resistance, considerably outperforming the 3.5-mm intramedullary screw (605.80 ± 165.11 N·mm) in fracture fixation strength. In the torsional stiffness assessment, both the one-third tubular plate (67.67 ± 15.39 N·mm, median ± interquartile range) and the 4.5-mm intramedullary headless compression screw (62.44 ± 17.36 N·mm) exhibited equivalent resistance and were substantially superior to the 3.5-mm intramedullary screw (25.90 ± 5.1 N·mm) in their ability to fix fractures. Conclusion The 4.5-mm intramedullary headless compression screw provides strong mechanical stability and a lower risk of soft tissue complications in clinical practice. Therefore, this headless compression screw can be recommended as a fixation option for Weber type B lateral malleolar fractures.